Characterization of the complete mitogenome of the estuarine benthic ribbon worm Yininemertes pratensis (Sun and Lu 1998) (Nemertea: Lineidae). Issue 10 (3rd October 2021) - Lee, Sang-Hwa; Seul, Yi; Kim, Kwang-Soo; Park, Taeseo
Abstract: The complete mitogenome of the estuarine ribbon worm Yininemertes pratensis (Sun and Lu 1998 ) (Nemertea: Lineidae) was sequenced for the first time in the present study. The total length of the newly sequenced mitogenome is 15, 616 bp, and it includes 13 protein-coding, 2 rRNA, and 24 tRNA genes, in addition to a noncoding region of 571 bp. The phylogenetic position of Y. pratensis was examined through maximum-likelihood analysis using a concatenated dataset of 13 protein-coding genes from seven selected nemertean species. Yininemertes pratensis is placed within the pilidiophoran group and is closely related to Lineus alborostratus among the selected nemerteans. The newly determined mitogenome sequence will further our knowledge for future phylogenetic and ecological studies of this species.